Holocaust and Parallax - Mayer, Gabriel (Advances in Social Sciences Research Journal, 2020)
Our objective is to demonstrate the shifting nature of Holocaust cultural memory and the attendant historiography as it accelerates in the chronotrope of present and future history. This is the manifestation of a parallax effect exacerbated and complicated by polity, transnational viewpoints on genocide, and the convenient utilization of a "unique event” as code language in real-time global politics and the necessities of economic value. What suffers is a myriad of cultural expressions ranging from literature to art and museology to heritage landscapes. This work leads into an expose to show how state actors transpose them into malevolent political tools and steal good-intentioned academic progress.